Offensive and defensive team performances: relation to successful and unsuccessful participation in the UEFA Champions League 20/21 - Anwar, M. Q. H. K.; Jamaludin, M.; Razali, M. R.; Talip, N. K. A.; Ismail, Z. (Journal of Physical Education and Sport, 2022)
The primary factor that determines a football team's performance is its ability to score goals. Due to the rarity of successfully scored goals in a match, it is vital for teams to consistently create scoring opportunities while preventing their opponents from doing the same. The purpose of this study is to determine (1) the effect of offensive and defensive performance indicators on a team`s success and (2) the impact of the `first goal effect` on the maches (for the team that scored the goal: win, draw or lose) in the UEFA Champions League 20/21. The sample of this study comprises 152 matches from the tournament's group and knockout phases. The performance indicators were fourteen selected offensive and defensive variables. The results of the study reveal that the successful teams had higher values (p < 0.05) in all offensive (except shots off goal for the team) and defensive (except the percentage of shots on goal against and percentage of shots off goal against) performance indicators than unsuccessful teams. In the group stage, the teams that scored first won 71.1% of their total matches (p < 0.001). In the knockout stage, the first goal effect had a greater impact on the outcome of matches than it did in the group stage (p < 0.001), as evidenced by the fact that, in 81.3% of the cases, the team that scored first won the match. Successful teams appear to perform better across the board in terms of offence and defence. This data directly impacts coaches, providing pertinent information for developing goal-scoring strategies.